2008
DOI: 10.1007/s00792-008-0184-4
|View full text |Cite
|
Sign up to set email alerts
|

Sulfobacillus benefaciens sp. nov., an acidophilic facultative anaerobic Firmicute isolated from mineral bioleaching operations

Abstract: Gram-positive bacteria found as the sole Firmicutes present in two mineral bioleaching stirred tanks, and a third bacterium isolated from a heap leaching operation, were shown to be closely related to each other but distinct from characterized acidophilic iron- and sulfur-oxidizing bacteria of the genus Sulfobacillus, to which they were affiliated. One of the isolates (BRGM2) was shown to be a thermo-tolerant (temperature optimum 38.5 degrees C, and maximum 47 degrees C) obligate acidophile (pH optimum 1.5, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…tend to be in lower relative abundance (4). Studies have indicated that species of Sulfobacillus are facultative anaerobes capable of both autotrophic and heterotrophic modes of growth (22,35). Oxidation of Fe(II), S 0 , and sulfide minerals, anaerobic reduction of Fe(III), and utilization of yeast extract, glucose, mannose, and other carbon sources have been described for various Sulfobacillus species (22,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tend to be in lower relative abundance (4). Studies have indicated that species of Sulfobacillus are facultative anaerobes capable of both autotrophic and heterotrophic modes of growth (22,35). Oxidation of Fe(II), S 0 , and sulfide minerals, anaerobic reduction of Fe(III), and utilization of yeast extract, glucose, mannose, and other carbon sources have been described for various Sulfobacillus species (22,35).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that species of Sulfobacillus are facultative anaerobes capable of both autotrophic and heterotrophic modes of growth (22,35). Oxidation of Fe(II), S 0 , and sulfide minerals, anaerobic reduction of Fe(III), and utilization of yeast extract, glucose, mannose, and other carbon sources have been described for various Sulfobacillus species (22,35). Sulfobacillus species were detected predominantly in 5-way biofilms, but we have not clearly identified ecological roles for these organisms: their broad metabolic capabilities may be indicative of a generalist ecological strategy.…”
Section: Discussionmentioning
confidence: 99%
“…To date, five species have been differentiated phenotypically as well as by 16S rRNA gene sequence analysis. Sulfobacillus thermosulfidooxidans (16) appears to be the most active in oxidation of iron and mineral sulfides and is commonly isolated from biomining operations, while S. benefaciens (19) has been less frequently isolated from similar processes. The species more commonly isolated from natural environments include Sulfobacillus acidophilus (30), Sulfobacillus sibiricus (26), and Sulfobacillus thermotolerans (4).…”
mentioning
confidence: 99%
“…benefaciens therefore favoured when growing in autotrophic conditions in continuous stirred tank system (Rawlings, 2005;Johnson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%